Engineers - Farndon, John.; Hart-Davis, Adam. (London DK Publishing, 2012)
Presents a history of the world's most prominent and revolutionary engineers, discussing their key feats and major breakthroughs, from Archimedes and Leonardo da Vinci to Henry Ford and the Wright brothers.
The early engineers -- Renaissance and enlightenment -- The industrial revolution -- The machine age -- Modern times.
Includes index.
Keywords: Engineers -- Biography; Engineering -- History